The Influence of Political Connection on Tax Avoidance - Zaga Kresna Pratama Putra; Novrys Suhardianto (Institute of Research and Community Outreach - Petra Christian University, 2020)
The upper echelon theory and rent-seeking theory propose conflicting arguments related to the relationship between a firm’s political connection and tax avoidance. This research aims to examine the relationship between a firm’s political connection and tax avoidance. The 1,079 samples used in this research are public companies with positive income in the 2014-2018 period. By using regression analysis, this research finds that political connection has a negative relationship with tax avoidance, implying that political connection increases tax payment. This research contributes to providing supporting evidence for upper echelon theory by finding that management’s political experience or the intention to maintain a positive image of politically connected management improves tax obedience